2020
DOI: 10.3390/nu12123796
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Obesity and Inflammatory Markers in the Development of Type 2 Diabetes in Men of Black African and White European Ethnicity

Abstract: In this study, we aimed to assess ethnic differences in visceral (VAT), deep subcutaneous (dSAT), and superficial subcutaneous (sSAT) adipose tissue and their relationships with inflammatory markers between white European (WE) and black West African (BWA) men with normal glucose tolerance (NGT) and type 2 diabetes (T2D). Forty-two WE (23 NGT/19 T2D) and 43 BWA (23 NGT/20 T2D) men underwent assessment of plasma inflammatory markers using immunoassays alongside Dixon magnetic resonance imaging to quantify L4-5 V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…As the CpG sites identified in this study were adjusted for cell composition which uses surrogate measures from six cell types [ 34 ], we may be identifying unique immune cell subsets associated with these disease exposures not captured by this method which may drive differences in outcomes. Additionally, several studies have also observed a unique relationship between inflammatory markers and adiposity in individuals of African descent, where these markers do not appear to be as sensitive to adiposity compared to individuals of European descent [ 35 , 36 ]. This may explain the significant differences observed when we exclude the ARIC AA cohort in sensitivity analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the CpG sites identified in this study were adjusted for cell composition which uses surrogate measures from six cell types [ 34 ], we may be identifying unique immune cell subsets associated with these disease exposures not captured by this method which may drive differences in outcomes. Additionally, several studies have also observed a unique relationship between inflammatory markers and adiposity in individuals of African descent, where these markers do not appear to be as sensitive to adiposity compared to individuals of European descent [ 35 , 36 ]. This may explain the significant differences observed when we exclude the ARIC AA cohort in sensitivity analyses.…”
Section: Discussionmentioning
confidence: 99%
“…When we adjusted for physical activity, no sites were significantly associated with BMI × MHZ. We included this analysis as several studies have touted that MHO may be the product of increased fitness in this population [ 36 , 37 ]. This may be due to true confounding by physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although small compared to most cardiovascular risk studies, the large effect size permits highly significant results. Secondly, only people of white European ethnicity were studied, reflecting the population of the North East of England, and specific studies are required to examine the biomarker relationships in other ethnicities [ 44 ]. Thirdly, our follow up period was short, and the study did not include a non-diabetic control group for comparison with the normal range in blood parameters and CVD risks.…”
Section: Discussionmentioning
confidence: 99%
“…IL, interleukin; VAT, visceral adipose tissue; VEGF, vascular endothelial growth factor; TNF-α, tumour necrosis factor alpha; IFN-ɣ, interferon gamma. Data from subjects included in this study have been previously published in [22][23][24]. A two-way betweengroup ANOVA was used to analyse the dependent variables of ethnicity and glucose tolerance on the outcome measures takes account of first-pass hepatic insulin extraction, which is not captured by the MCRI.…”
Section: Discussionmentioning
confidence: 99%
“…The SouL-DeEP study was an observational cross-sectional study aimed at exploring ethnic differences in a range of mechanisms underlying the development of T2D between men of WE and BA ethnicity with NGT and early T2D. The study was designed to enable the exploration of a wide range of hypotheses, several of which have been published [22][23][24]. Data collection took place between April 2013 and April 2019.…”
Section: Methodsmentioning
confidence: 99%